Advances in Computational Methods in Manufacturing Select Papers from ICCMM 2019 - Narayanan, R. Ganesh; Joshi, Shrikrishna N.; Dixit, Uday Shanker (Lecture Notes on Multidisciplinary Industrial Engineering, 2019)
This volume presents a selection of papers from the 2nd International Conference on Computational Methods in Manufacturing (ICCMM 2019). The papers cover the recent advances in computational methods for simulating various manufacturing processes like machining, laser welding, laser bending, strip rolling, surface characterization and measurement. Articles in this volume discuss both the development of new methods and the application and efficacy of existing computational methods in manufacturing sector. This volume will be of interest to researchers in both industry and academia working on computational methods in manufacturing.